The value chain of foreign aid : development, poverty reduction, and regional conditions - Schabbel, Christian (Contributions to economics., 2007)
"This book assesses the prospects of ODA for poverty reduction. The author analyzes the entire value chain of ODA, including the provision, allocation and utilization. Within each of these components, scope and limits of aid are critically examined."--Jacket